Prickly sea stars - Lunis, Natalie (New York, NY : Bearport, 2008)
Text and photographs present amazing facts about sea stars.
Includes bibliographical references (p. 24) and index.
8 13
Keywords: Starfishes -- Juvenile literature; Starfishes